Butyrate SiO2 / modified starch blend slurry, preparation method and application
By using butyrate-esterified SiO2/modified starch blend slurry in the textile slurry, the shortcomings of the existing textile slurry in improving the mechanical properties and wear resistance of warp yarns are solved, and higher wear resistance, fracture strength and hair reduction rate are achieved.
Patent Information
- Application Number
- CN202310510216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-08
AI Technical Summary
The existing textile slurries have shortcomings in improving the mechanical properties and wear resistance of warp yarns, resulting in a decrease in weaving efficiency and product quality.
The blended slurry of butyrate esterified SiO2/modified starch is prepared by esterification modification of nano SiO2 and compound chemical modification of starch, which significantly improves the water dispersion and uniformity of nano SiO2.
The wear resistance, fracture strength and hair reduction rate of the spinning are significantly improved, and the film forming properties and mechanical properties of the slurry are improved.
Smart Images

Figure CN116397434B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of textile technology, in particular to butyrate-esterified SiO 2 / Modified starch blend slurry, preparation method and application. Background Art
[0002] There are a lot of hairiness on the surface of the raw yarn, and the cohesion between the fibers is low. In addition, during the weaving production process, the warp yarns rub against each other, and the mechanical parts will repeatedly rub, stretch and bend the warp yarns, which will cause the warp yarns to break and form hair balls, resulting in a significant reduction in weaving efficiency and product quality.
[0003] In order to improve the mechanical properties and wear resistance of the warp yarn, sizing is mainly used. During the sizing process of the warp yarn, part of the sizing will penetrate into the inside of the warp yarn, forming an adhesive layer between the internal fibers, which plays a role in bonding and improving the strength of the warp yarn; the other part of the sizing will be dried on the surface of the warp yarn to form a uniform sizing film, which makes the surface hairiness flat and the warp yarn surface smooth, thereby improving the wear resistance of the warp yarn.
[0004] The current textile pulp mainly consists of nano-SiO 2 Added as an additive to starch slurry to prepare nano-SiO 2 / starch blended slurry to make up for the defects of starch slurry, promote the adhesion of starch to fiber, improve the starch film properties, and improve the sizing performance. For example, in 2006, Yang studied nano-SiO 2 The effect of modified epoxy emulsion sizing on the interfacial bonding properties of carbon fiber reinforced composites was studied. The results showed that after sizing, the number of hydroxyl groups on the carbon fiber surface increased slightly; compared with the unsized CFRP, the interlaminar shear strength (ILSS) of the CFRP treated with unmodified sizing increased by 9%, and the modified nano-SiO 2 The ILSS of CFRP after slurry treatment increased by 14%, and no holes or carbon fiber pull-out were observed on the fracture surface. 2 The cross section of CFRP treated with modified slurry is more compact and fiber debonding is more difficult. 2 As a filler, it was added into starch slurry. Sizing experiments were carried out on pure cotton yarn and polyester / cotton blended yarn with different linear densities. 2 The effect of the dosage on the sizing properties of starch. The results show that: 2 After that, the wear resistance, breaking strength and hairiness reduction rate of the sizing yarn are improved to a certain extent; Nano-SiO 2 The amount of starch used will have a certain impact on the actual sizing effect, and 3% to 4% is appropriate.
[0005] Nano-SiO 2 As an additive, it can effectively improve the performance of the slurry and have a positive impact on the sizing effect. The purpose of the present invention is to improve the performance of the slurry by adding nano-SiO 2 After the starch is modified, a blended slurry is prepared to further improve the sizing performance. Summary of the invention
[0006] Based on the technical problems existing in the background technology, the present invention proposes a butyrate-esterified SiO 2 / modified starch blended slurry, preparation method and application thereof; the spinning treated with the slurry significantly improves the wear resistance, breaking strength and hairiness reduction rate.
[0007] The butyrate SiO 2 / A method for preparing a modified starch blend slurry, the method steps are as follows:
[0008] S1: Preparation of modified starch QBS;
[0009] S2: Butyrate SiO 2 Preparation
[0010] Nano-SiO 2 It is mixed with distilled water to form a dispersion, butyric anhydride is added and reacted under alkaline conditions, and after the reaction, butyric acid esterified SiO is obtained after washing and drying. 2 ;
[0011] S3: Preparation of blended slurry
[0012] Butyrate SiO in S2 2 The mixture is mixed with distilled water to form a dispersion, and then the modified starch QBS in S1 is added and mixed evenly to obtain a blended slurry.
[0013] Preferably, the preparation method of the modified starch QBS comprises the following steps:
[0014] S11: dispersing corn starch in distilled water, adding dilute hydrochloric acid to react, neutralizing with alkali, filtering, washing, drying and crushing after the reaction to obtain acid-decomposed starch ATS;
[0015] S12: Disperse the acid-decomposed starch from S11 in a solution containing Na 2 SO 4 distilled water, and adjusting the pH to 10-11, then sequentially adding a mixed solution of a cationic etherifying agent and NaOH and an aqueous solution of CaO to react, and after the reaction, neutralizing with acid, washing, drying and crushing, obtaining quaternary ammonium cationic starch QS;
[0016] S13: The quaternary ammonium cationic starch QS of S12 is dispersed in distilled water and the pH is adjusted to 8-9, and then butyric anhydride is added to react. After the reaction, the modified starch QBS is obtained after acid neutralization, washing, drying and crushing.
[0017] Preferably, the mass ratio of ATS, cationic etherifying agent and CaO in S12 is 324:5-50:0.5-2.5.
[0018] Preferably, the mass ratio of QS to butyric anhydride in S13 is 200:1-15.
[0019] Preferably, nano-SiO 2 The mass ratio of butyric anhydride to butyric anhydride is 4:1-24.
[0020] Preferably, the reaction conditions in S2 are: temperature 70-90° C., time 80-120 min.
[0021] Preferably, the drying temperature in S2 is 50-70° C. and the drying time is 20-28 h.
[0022] Preferably, the butyrate-esterified SiO in S3 2 The mass ratio of modified starch QBS is 0.25-1.5:100.
[0023] The butyrate SiO prepared by the above method proposed in the present invention 2 / modified starch blended slurry.
[0024] The butyrate SiO 2 / Application of modified starch blended slurry in textiles.
[0025] Beneficial technical effects of the present invention:
[0026] The conventional method is to use nano-SiO 2 Directly add to unmodified starch for blending to prepare nano-SiO 2 / starch blended slurry, and then used. The present invention adopts the method of firstly treating the nano-SiO 2 After esterification and composite chemical modification of starch, butyrate-esterified SiO 2 and modified starch QBS, butyrate SiO 2 The mixture was mixed with distilled water to form a dispersion, and then the modified starch QBS was added and mixed evenly to obtain a blended slurry. 2 The water dispersibility and significant reduction of nano-SiO 2 The particle size of the aggregates has greatly increased the 2 The uniformity of dispersion in the blended slurry and its degree of combination with starch; butyrate SiO 2The ester group in the butyrate substituent has chemical similarity with the ester group in the modified starch QBS substituent and the ester group in the polyester fiber, so that a strong van der Waals force can be generated between the three. 2 Adhesion performance of / modified starch blended slurry to polyester fiber and nano-SiO 2 / modified starch blended slurry, it has been greatly improved.
[0027] SiO 2 Modified butyrate SiO 2 It can be better dispersed in the modified starch QBS with ester group. Due to its small size effect and macro quantum tunneling effect, it can produce siltation and penetrate into the QBS macromolecular chain to form a spatial network structure. At the same time, butyrate esterified SiO 2 / modified starch blended film has a higher moisture regain, which improves the plasticizing effect of water on the blended film, thus compared with QBS (accounting for 0% of starch mass), nano-SiO 2 / QBS, butyrate SiO 2 The slurry of QBS / modified starch blended slurry has better film-forming property and better mechanical properties of the slurry film.
[0028] In summary, nano-SiO 2 Butyrate modification can greatly improve its performance as a blending slurry component. Based on various performance results, the present invention also points out that in butyrate modification of SiO 2 Butyrate-esterified SiO2 in / modified starch blend slurry 2 The performance is relatively excellent when the dosage is 1%. The blended slurry of the present invention will give spinning better abrasion resistance, breaking strength and hairiness reduction rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The nano-SiO 2 and butyrate SiO 2 Infrared spectrum of
[0030] Figure 2 The nano-SiO 2 and butyrate SiO 2 TEM image; a is nano-SiO 2 , b is butyrate SiO 2 ;
[0031] Figure 3 The nano-SiO 2 and butyrate SiO 2 Particle size distribution diagram;
[0032] Figure 4 The different nano-SiO 2 and butyrate SiO 2 The apparent viscosity of the blended slurry under the added amount;
[0033] Figure 5 The different nano-SiO 2 and butyrate SiO 2 Adhesion of the added amount of blended slurry to polyester fiber;
[0034] Figure 6 The different nano-SiO 2 and butyrate SiO 2 The breaking strength of the blended slurry film with the added amount;
[0035] Figure 7 The different nano-SiO 2 and butyrate SiO 2 Elongation at break of blended slurry film with added amount;
[0036] Figure 8 The different nano-SiO 2 and butyrate SiO 2 Moisture regain of blended slurry film with added amount. DETAILED DESCRIPTION
[0037] Example 1
[0038] The SiO 2 - A method for preparing a g-PAA / modified starch blend slurry, the method steps are as follows:
[0039] S1: Preparation of modified starch QBS
[0040] Weigh 400g of corn starch with a dry weight and disperse it in distilled water to prepare a 40% starch milk, transfer it to a three-necked flask, set the water bath temperature to 50°C, and control the stirring rod speed to 130r / min. When the water bath temperature reaches 50°C, slowly add 37mL of a 2mol / L dilute HCl solution with a separatory funnel, and count for 4 hours after the addition is completed. After the reaction is completed, add a 1mol / L NaOH solution to neutralize the starch milk to a pH of 6-7, filter, wash with distilled water, and vacuum filter. After repeating the operation 4 times, place it in a blast dryer to dry, crush it with an ultrafine grinder, and seal it in a bag for standby use to obtain acid-decomposed starch (ATS).
[0041] Weigh 324 g of dry weight of ATS and disperse it in a solution containing Na 2 SO 4distilled water, stirred evenly and then transferred into a three-necked flask, the pH value was adjusted to 10-11 with 3% NaOH solution, heated to 40°C with stirring, and a mixed solution containing equimolar cationic etherifying agent and NaOH was added (added within 1 min), and 30 mL of an aqueous solution containing 1.8 g CaO was added after 10 min. After reacting for 8 h, the solution was neutralized with 2 mol / L HCl solution to a pH value of 6-7, filtered and washed 2-3 times, dried in a blast dryer, crushed with an ultrafine grinder, and sealed in bags for standby use to obtain quaternary ammonium cationic starch (QS).
[0042] Weigh 120 g of QS with dry weight and mix it with distilled water to form a starch dispersion with a mass fraction of 40%. 2 CO 3 After the solution adjusts the pH value of the dispersion to 8-9, heat it to 30°C in a water bath under stirring. Use a separatory funnel to slowly drop the butyric anhydride solution into the dispersion, and use the above-mentioned alkaline solution to maintain the pH value at 8-9. After the dropwise addition is completed, continue to stir and react for 0.5h. Use a 2mol / L HCl solution to adjust the pH value of the reaction system to 6.5-7, filter it, wash it 3 times, dry it, and crush it to obtain modified starch QBS.
[0043] S2: Butyrate SiO 2 Preparation
[0044] Add 4 g of dry nano-SiO into a 250 mL three-necked flask. 2 The particles were mixed with distilled water to form a 1% dispersion, 20g of butyric anhydride was slowly added, and magnetic stirring was used to accelerate the mixing. The reaction was controlled under alkaline conditions in a constant temperature water bath at 85°C, and the reaction time was 100min. After the experiment was completed, the particles were washed 4 times by centrifugation with anhydrous ethanol, and then washed by centrifugation with distilled water, and placed in a 60°C oven to dry for 24h to obtain butyric acid esterified SiO 2 .
[0045] S3: Preparation of blended slurry
[0046] 0.25 g of butyrate-esterified SiO in S2 2 Prepare a dispersion with distilled water, then add 100g of modified starch QBS in S1 and mix evenly to obtain a blended slurry.
[0047] Example 2
[0048] The SiO 2 - A method for preparing a g-PAA / modified starch blend slurry, the method steps are as follows:
[0049] S1: Preparation of modified starch QBS
[0050] Weigh 400g of corn starch with a dry weight and disperse it in distilled water to prepare a 40% starch milk, transfer it to a three-necked flask, set the water bath temperature to 50°C, and control the stirring rod speed to 130r / min. When the water bath temperature reaches 50°C, slowly add 37mL of a 2mol / L dilute HCl solution with a separatory funnel, and count for 4 hours after the addition is completed. After the reaction is completed, add a 1mol / L NaOH solution to neutralize the starch milk to a pH of 6-7, filter, wash with distilled water, and vacuum filter. After repeating the operation 4 times, place it in a blast dryer to dry, crush it with an ultrafine grinder, and seal it in a bag for standby use to obtain acid-decomposed starch (ATS).
[0051] Weigh 324 g of dry weight of ATS and disperse it in a solution containing Na 2 SO 4 distilled water, stirred evenly and then transferred into a three-necked flask, the pH value was adjusted to 10-11 with 3% NaOH solution, heated to 40°C with stirring, and a mixed solution containing equimolar cationic etherifying agent and NaOH was added (added within 1 min), and 30 mL of an aqueous solution containing 1.8 g CaO was added after 10 min. After reacting for 8 h, the solution was neutralized with 2 mol / L HCl solution to a pH value of 6-7, filtered and washed 2-3 times, dried in a blast dryer, crushed with an ultrafine grinder, and sealed in bags for standby use to obtain quaternary ammonium cationic starch (QS).
[0052] Weigh 120 g of QS with dry weight and mix it with distilled water to form a starch dispersion with a mass fraction of 40%. 2 CO 3 After the solution adjusts the pH value of the dispersion to 8-9, heat it to 30°C in a water bath under stirring. Use a separatory funnel to slowly drop the butyric anhydride solution into the dispersion, and use the above-mentioned alkaline solution to maintain the pH value at 8-9. After the dropwise addition is completed, continue to stir and react for 0.5h. Use a 2mol / L HCl solution to adjust the pH value of the reaction system to 6.5-7, filter it, wash it 3 times, dry it, and crush it to obtain modified starch QBS.
[0053] S2: Butyrate SiO 2 Preparation
[0054] Add 4 g of dry nano-SiO into a 250 mL three-necked flask. 2 The particles were mixed with distilled water to form a 1% dispersion, 20g of butyric anhydride was slowly added, and magnetic stirring was used to accelerate the mixing. The reaction was controlled under alkaline conditions in a constant temperature water bath at 85°C, and the reaction time was 100min. After the experiment was completed, the particles were washed 4 times by centrifugation with anhydrous ethanol, and then washed by centrifugation with distilled water, and placed in a 60°C oven to dry for 24h to obtain butyric acid esterified SiO 2 .
[0055] S3: Preparation of blended slurry
[0056] 0.5 g of butyrate-esterified SiO in S2 2 Prepare a dispersion with distilled water, then add 100g of modified starch QBS in S1 and mix evenly to obtain a blended slurry.
[0057] Example 3
[0058] The SiO 2 - A method for preparing a g-PAA / modified starch blend slurry, the method steps are as follows:
[0059] S1: Preparation of modified starch QBS
[0060] Weigh 400g of corn starch with a dry weight and disperse it in distilled water to prepare a 40% starch milk, transfer it to a three-necked flask, set the water bath temperature to 50°C, and control the stirring rod speed to 130r / min. When the water bath temperature reaches 50°C, slowly add 37mL of a 2mol / L dilute HCl solution with a separatory funnel, and count for 4 hours after the addition is completed. After the reaction is completed, add a 1mol / L NaOH solution to neutralize the starch milk to a pH of 6-7, filter, wash with distilled water, and vacuum filter. After repeating the operation 4 times, place it in a blast dryer to dry, crush it with an ultrafine grinder, and seal it in a bag for standby use to obtain acid-decomposed starch (ATS).
[0061] Weigh 324 g of dry weight of ATS and disperse it in a solution containing Na 2 SO 4 distilled water, stirred evenly and then transferred into a three-necked flask, the pH value was adjusted to 10-11 with 3% NaOH solution, heated to 40°C with stirring, and a mixed solution containing equimolar cationic etherifying agent and NaOH was added (added within 1 min), and 30 mL of an aqueous solution containing 1.8 g CaO was added after 10 min. After reacting for 8 h, the solution was neutralized with 2 mol / L HCl solution to a pH value of 6-7, filtered and washed 2-3 times, dried in a blast dryer, crushed with an ultrafine grinder, and sealed in bags for standby use to obtain quaternary ammonium cationic starch (QS).
[0062] Weigh 120 g of QS with dry weight and mix it with distilled water to form a starch dispersion with a mass fraction of 40%. 2 CO 3After the solution adjusts the pH value of the dispersion to 8-9, heat it to 30°C in a water bath under stirring. Use a separatory funnel to slowly drop the butyric anhydride solution into the dispersion, and use the above-mentioned alkaline solution to maintain the pH value at 8-9. After the dropwise addition is completed, continue to stir and react for 0.5h. Use a 2mol / L HCl solution to adjust the pH value of the reaction system to 6.5-7, filter it, wash it 3 times, dry it, and crush it to obtain modified starch QBS.
[0063] S2: Butyrate SiO 2 Preparation
[0064] Add 4 g of dry nano-SiO into a 250 mL three-necked flask. 2 The particles were mixed with distilled water to form a 1% dispersion, 20g of butyric anhydride was slowly added, and magnetic stirring was used to accelerate the mixing. The reaction was controlled under alkaline conditions in a constant temperature water bath at 85°C, and the reaction time was 100min. After the experiment was completed, the particles were washed 4 times by centrifugation with anhydrous ethanol, and then washed by centrifugation with distilled water, and placed in a 60°C oven to dry for 24h to obtain butyric acid esterified SiO 2 .
[0065] S3: Preparation of blended slurry
[0066] 1.0 g of butyrate-esterified SiO in S2 2 Prepare a dispersion with distilled water, then add 100g of modified starch QBS in S1 and mix evenly to obtain a blended slurry.
[0067] Example 4
[0068] The butyrate SiO 2 / A method for preparing a modified starch blend slurry, the method steps are as follows:
[0069] S1: Preparation of modified starch QBS
[0070] Weigh 400g of corn starch with a dry weight and disperse it in distilled water to prepare a 40% starch milk, transfer it to a three-necked flask, set the water bath temperature to 50°C, and control the stirring rod speed to 130r / min. When the water bath temperature reaches 50°C, slowly add 37mL of a 2mol / L dilute HCl solution with a separatory funnel, and count for 4 hours after the addition is completed. After the reaction is completed, add a 1mol / L NaOH solution to neutralize the starch milk to a pH of 6-7, filter, wash with distilled water, and vacuum filter. After repeating the operation 4 times, place it in a blast dryer to dry, crush it with an ultrafine grinder, and seal it in a bag for standby use to obtain acid-decomposed starch (ATS).
[0071] Weigh 324 g of dry weight of ATS and disperse it in a solution containing Na 2 SO 4distilled water, stirred evenly and then transferred into a three-necked flask, the pH value was adjusted to 10-11 with 3% NaOH solution, heated to 40°C with stirring, and a mixed solution containing equimolar cationic etherifying agent and NaOH was added (added within 1 min), and 30 mL of an aqueous solution containing 1.8 g CaO was added after 10 min. After reacting for 8 h, the solution was neutralized with 2 mol / L HCl solution to a pH value of 6-7, filtered and washed 2-3 times, dried in a blast dryer, crushed with an ultrafine grinder, and sealed in bags for standby use to obtain quaternary ammonium cationic starch (QS).
[0072] Weigh 120 g of QS with dry weight and mix it with distilled water to form a starch dispersion with a mass fraction of 40%. 2 CO 3 After the solution adjusts the pH value of the dispersion to 8-9, heat it to 30°C in a water bath under stirring. Use a separatory funnel to slowly drop the butyric anhydride solution into the dispersion, and use the above-mentioned alkaline solution to maintain the pH value at 8-9. After the dropwise addition is completed, continue to stir and react for 0.5h. Use a 2mol / L HCl solution to adjust the pH value of the reaction system to 6.5-7, filter it, wash it 3 times, dry it, and crush it to obtain modified starch QBS.
[0073] S2: Butyrate SiO 2 Preparation
[0074] Add 4 g of dry nano-SiO into a 250 mL three-necked flask. 2 The particles were mixed with distilled water to form a 1% dispersion, 20g of butyric anhydride was slowly added, and magnetic stirring was used to accelerate the mixing. The reaction was controlled under alkaline conditions in a constant temperature water bath at 85°C, and the reaction time was 100min. After the experiment was completed, the particles were washed 4 times by centrifugation with anhydrous ethanol, and then washed by centrifugation with distilled water, and placed in a 60°C oven to dry for 24h to obtain butyric acid esterified SiO 2 .
[0075] S3: Preparation of blended slurry
[0076] 1.5 g of butyrate-esterified SiO in S2 2 Prepare a dispersion with distilled water, then add 100g of modified starch QBS in S1 and mix evenly to obtain a blended slurry.
[0077] Figure 1 Nano-SiO 2 and the butyrate SiO prepared in Example 3 2 Infrared spectrum of nano-SiO 2 Compared with the infrared spectrum curve of butyrate-treated SiO 2 The spectrum curve is at 1733cm -1The characteristic peak of ester carbonyl was generated at the position of the nanostructured butyrate, proving that the hydrophobic butyrate substituent was successfully introduced into the nano-SiO 2 The butyrate-treated SiO 2 Successful preparation.
[0078] Figure 2 Nano-SiO 2 and the butyrate SiO prepared in Example 3 2 TEM image of Figure 2 (a) It can be seen that nano-SiO 2 The primary particles are spherical with a particle size of 15-20 nm. The particles are interconnected to form a network structure. 2 The degree of clustering is high. Figure 2 (b) It can be seen that the modified butyrate SiO 2 Obviously the dispersion is better and the degree of agglomeration is reduced.
[0079] Figure 3 Nano-SiO 2 and butyrate SiO 2 Particle size distribution diagram of nano-SiO 2 The particle size distribution of the agglomerates is wide and uneven, and the diameter of the agglomerates is concentrated in 300-400nm, indicating that the nano-SiO 2 In aqueous solution, the particles agglomerated seriously and there were large agglomerated particles. 2 The diameter of the agglomerates is concentrated in the range of 120-180 nm, the average particle size is significantly reduced, and the particle size distribution is more uniform. 2 The dispersion in the blended slurry will be greatly improved and the dispersion stability will be enhanced.
[0080] Figure 4 Nano-SiO 2 / QBS and butyrate-esterified SiO 2 The apparent viscosity of the / QBS blend slurry increases with the increase of the amount of nano-additive. 2 The apparent viscosity of the / QBS blend slurry did not change much, increasing from 7mPa·s to 9.5mPa·s; the butyrate-esterified SiO 2 The apparent viscosity of the / QBS blend slurry increased from 7mPa·s to 10.7mPa·s. 2 The apparent viscosity of the / QBS blended slurry is slightly higher than that of nano-SiO 2 / QBS blended slurry is due to: the modified nano-SiO 2It has better dispersibility in aqueous solution, can better exert its volume effect, increase the distance between starch macromolecules, thereby further swelling starch granule fragments, further stretching the molecular chains, increasing the dynamic volume of starch macromolecular coils, and enhancing the resistance to slurry flow.
[0081] Figure 5 Nano-SiO 2 / QBS and butyrate-esterified SiO 2 Adhesion results between / QBS blended slurry and polyester fiber. 2 The adhesion of / QBS blended slurry to polyester fiber is better than that of nano-SiO 2 / QBS. Modified butyrate SiO 2 The dispersion is better and the contact area with the starch matrix is larger. When the roving is stretched and breaks, the microcracks that will be generated during the stretching can be stopped in time to prevent them from turning into destructive cracks. In addition, according to the principle of "like is compatible", butyrate-esterified SiO 2 The introduction of hydrophobic butyrate substituents on the surface will produce a certain affinity for polyester fibers. 2 The adhesion of / QBS blended slurry to polyester fiber is better than that of nano-SiO 2 / QBS. When butyrate-esterified SiO 2 Nano-additive butyrate-esterified SiO in QBS blend slurry 2 The dosage of 1% has the greatest effect on improving adhesion.
[0082] Figure 6 and Figure 7 The nano-SiO 2 / QBS and butyrate-esterified SiO 2 / QBS blended slurry film. With the increase of nano additive dosage, nano-SiO 2 The breaking strength of the / QBS blend film decreased from 32.7MPa to 26.5MPa (at 1%), and then increased, while the breaking elongation increased from 2.96% to 3.55% (at 1%), and then decreased. 2 The breaking strength of the / QBS blend film decreased from 32.7MPa to 22.2MPa (at 1%), and then increased, while the breaking elongation increased from 2.96% to 3.61% (at 1%), and then decreased. 2 / QBS blended slurry membrane has better mechanical properties.
[0083] Butyrate SiO 2The / QBS blended slurry membrane has better mechanical properties because the butyrate-modified SiO 2 It can be better dispersed evenly in the QBS slurry. Due to its small size effect and macro quantum tunneling effect, it can produce a siltation effect and penetrate into the QBS macromolecular chains to form a spatial network structure. 2 / QBS, butyrate SiO 2 / QBS blend slurry has better film-forming properties and the slurry film will be more flexible.
[0084] Figure 8 It reflects the different dosages of nano-auxiliaries. 2 / QBS, butyrate SiO 2 / QBS blended slurry film moisture regain. As can be seen from the figure, nano-SiO 2 / QBS regain increases with the change of nano-SiO 2 The content of butyrate-containing SiO 2 The moisture regain of the / QBS blended film gradually increases with the increase of the amount of nano-additive (0-1.5%). When the amount is 1%, the moisture regain reaches the maximum value and then tends to be flat. 2 The moisture regain of the / QBS blended film is significantly higher than that of nano-SiO 2 / QBS blended pulp film.
[0085] The reason for the analysis is that nano-SiO 2 There are many hydrophilic hydroxyl groups on the surface, which can associate with the polar functional groups on the starch molecular chain to form a relatively tight network structure, which will make the surface of the serous membrane denser. A dense surface is not conducive to the penetration of water, so nano-SiO 2 / QBS has a lower moisture regain. Butyrate-treated SiO 2 The surface hydroxyl groups were partially replaced by butyrate substituents, and the association with the polar functional groups on the starch molecular chain was weakened; after chemical modification, the nano-SiO 2 The degree of agglomeration is reduced, and the small size effect in the QBS slurry is enhanced, which further hinders the association of hydroxyl groups between starch molecules and is not conducive to the formation of a dense slurry film, making it easier for water molecules to combine with starch molecules in the blended slurry film. 2 The moisture regain of the / QBS blended film is significantly higher than that of nano-SiO 2 / QBS blended pulp film.
Claims
1. A method for preparing a butyrate SiO2 / modified starch blend slurry, characterized in that: The steps are as follows: S1: Preparation of modified starch QBS; S2: Preparation of butyrate-esterified SiO2 Prepare nano-SiO2 and distilled water into a dispersion, add butyric anhydride and react under alkaline conditions, wash and dry after the reaction to obtain butyric acid esterified SiO2; S3: Preparation of blended slurry The butyrated SiO2 in S2 is mixed with distilled water to form a dispersion, and then the modified starch QBS in S1 is added and mixed evenly to obtain a blended slurry; The preparation method of the modified starch QBS has the following steps: S11: dispersing corn starch in distilled water, adding dilute hydrochloric acid to react, neutralizing with alkali, filtering, washing, drying and crushing after the reaction to obtain acid-decomposed starch ATS; S12: dispersing the acid-hydrolyzed starch of S11 in distilled water containing Na2SO4, adjusting the pH to 10-11, and then sequentially adding a mixed solution of a cationic etherifying agent and NaOH and an aqueous solution of CaO to react, neutralizing with acid, washing, drying and crushing after the reaction, to obtain quaternary ammonium cationic starch QS; S13: The quaternary ammonium cationic starch QS of S12 is dispersed in distilled water and the pH is adjusted to 8-9, and then butyric anhydride is added to react. After the reaction, the modified starch QBS is obtained after acid neutralization, washing, drying and crushing.
2. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The mass ratio of ATS, cationic etherifying agent and CaO in S12 is 324:5-50:0.5-2.
5.
3. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The mass ratio of QS to butyric anhydride in S13 is 200:1-15.
4. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The mass ratio of nano-SiO2 and butyric anhydride in S2 is 4:1~24.
5. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The reaction conditions in S2 are: temperature 70-90°C, time 80-120 min.
6. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The drying temperature in S2 is 50-70°C and the drying time is 20-28h.
7. The method for preparing the butyrated SiO2 / modified starch blend slurry according to claim 1, characterized in that: The mass ratio of butyrated SiO2 and modified starch QBS in S3 is 0.25-1.5:
100.
8. A butyrated SiO2 / modified starch blend slurry prepared according to the method of any one of claims 1 to 7.
9. Use of the butyrated SiO2 / modified starch blend slurry as claimed in claim 8 in polyester fiber.